Analisis Penerimaan OS Windows 10 Dengan Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) - Mega Shero Gayatrie; Ari Kusyanti; Mochamad Chandra Saputra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
This study discusses the acceptance of Windows 10 as operating system for desktop. This study is based on the seven constructs of the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) from Venkatesh et al. (2012) without moderate constructs who processed with Structural Equation Model (SEM). The respondents were teenage users in Indonesia. The result showed that effort expectancy, facilitating condition and price value do not have a significant positive impact on behavioral intentions while performance expectancy, social influence, hedonic motivation and habit had a significant positive effect on behavior intention. On the other hand, facilitating condition and habit factors influence use behavior while behavior intention do not have a positive impact on use behaviour to use Windows 10.